2021
DOI: 10.1038/s41421-021-00268-z
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 protein ORF3a inhibits fusion of autophagosomes with lysosomes

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the ongoing coronavirus disease 2019 pandemic. How SARS-CoV-2 regulates cellular responses to escape clearance by host cells is unknown. Autophagy is an intracellular lysosomal degradation pathway for the clearance of various cargoes, including viruses. Here, we systematically screened 28 viral proteins of SARS-CoV-2 and identified that ORF3a strongly inhibited autophagic flux by blocking the fusion of autophagosomes with lysosomes. ORF3a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
227
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(236 citation statements)
references
References 71 publications
9
227
0
Order By: Relevance
“…(Wang et al, 2021). Recent study showed that SARS-CoV-2 ORF3a blocks autophagosome maturation by blocking HOPSmediated SNARE complex assembly (Miao et al, 2021;Zhang et al, 2021), suggesting ORF3a may target multiple protein complexes required for autophagosome-lysosome fusion to facilitate SARS-CoV-2 replication. Given autophagy's role in the innate antiviral immune response to restrict infecting pathogens, it is not surprising that viruses are in a constant arms race to remodel the autophagic membranes for their own benefit during replication (Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wang et al, 2021). Recent study showed that SARS-CoV-2 ORF3a blocks autophagosome maturation by blocking HOPSmediated SNARE complex assembly (Miao et al, 2021;Zhang et al, 2021), suggesting ORF3a may target multiple protein complexes required for autophagosome-lysosome fusion to facilitate SARS-CoV-2 replication. Given autophagy's role in the innate antiviral immune response to restrict infecting pathogens, it is not surprising that viruses are in a constant arms race to remodel the autophagic membranes for their own benefit during replication (Choi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, nsp6 homologs from multiple coronaviruses, such as avian coronavirus, mouse hepatitis virus, SARS-CoV, and SARS-CoV-2, affect autophagosome membrane expansion, resulting in small autophagosome (Cottam et al, 2014). Besides nsp6 and ORF3a, ORF7a, and M of SARS-CoV-2 also inhibit autophagy at different levels, while within SARS-CoV-2-encoded proteins, ORF3a shows the most potent capability on autophagy modulation (Miao et al, 2021;Zhang et al, 2021). Manipulation of cellular autophagy pathway is a common signature of coronaviruses and ORF3a is a potential target to limit SARS-CoV-2 replication.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies uncovered the detailed mechanism of how SARS-CoV-2 p3a blocks autophagy [26,35,38,39]. Interestingly, autophagy induction by starvation, INK128, and blocks autophagosome turnover by p3a, p7a, and E protein (not shown).…”
Section: Protein 3a Affects Autophagosome/amphisome-lysosome Fusionmentioning
confidence: 98%
“…This block is consistent with SARS-CoV-2 infection in Calu-3 and Caco-2 cells that caused increased levels of both LC3-II and SQSTM1 [35]. Three viral proteins might be responsible for such a block: p3a, p7a, and envelope (E) protein (with p3a being the most prominent), because they were able to cause decreased autophagosome turnover (increased levels of LC3-II and SQSTM1) during ectopic expression in HEK293T, HeLa, and A549 cells [35,38,39]. Interestingly, a couple of SARS-CoV-2 proteins (NSP6 and p3a) can interact with and/or control the levels of select autophagic proteins [26].…”
Section: Proteins 3a 7a and E Block Autophagosome Turnovermentioning
confidence: 99%
“…The SARS-CoV-2 ORF3a protein, which presents 72.4% a.a identity with the SARS-CoV-1 ORF3a protein and 97.8% with the bat-SL-CoV-RaTG13 ORF3a, retains six functional domains (I-VI) (Figure 4A and Supplementary Table 1). These functional domains are linked to virulence, infectivity, ion channel formation and virus release (Issa et al, 2020;Kern et al, 2020) and as the ORF3a protein of SARS-CoV-1, the ORF3a protein SARS-CoV-2 retains the capacity to induce apoptosis (Ren et al, 2020) and also to inhibit fusion autophagosomes with lysosomes (Zhang et al, 2021b).…”
Section: Orf3a and 3b Proteinsmentioning
confidence: 99%